Voluntary running partially prevents photoreceptor cell death in retinitis pigmentosa - Agadagba, Stephen K.; Liang, Ying; Dalton, Kristine N.; Thompson, Benjamin; Yau, Suk-Yu (Frontiers in Neuroscience, 2025)
Retinitis pigmentosa (RP) is a progressive retinal degenerative disorder characterized by photoreceptor cell death, leading to vision loss. Current treatments are limited, and there is a need for non-invasive interventions. This study evaluates the neuroprotective effects of voluntary exercise in an RP mouse model and explores the role of the adiponectin signaling pathway in mediating these effects. Pregnant Pde6brd10 (rd10) mice, a transgenic model of RP, and wild-type C57BL/6J mice were divided into sedentary or voluntary running groups (n = 4 per group). Offspring were analyzed at 6 weeks for photoreceptor nuclei counts, outer segment lengths, serum and retinal adiponectin levels, and expression of AMPK and PGC-1α proteins using immunohistochemistry, ELISA, and Western blotting. Voluntary exercise significantly preserved photoreceptor nuclei (97 ± 16 vs. 32 ± 5 in sedentary rd10 mice) and outer segment lengths for rods (13.1 ± 1.2 μ vs. 1.1 ± 0.6 μ) and cones (7 ± 0.9 μ vs. 0.2 ± 0.1 μm) compared to sedentary rd10 mice. Serum adiponectin levels increased significantly in exercised rd10 mice (p < 0.05), while retinal adiponectin levels were elevated in both sedentary and exercised rd10 mice relative to wild-type controls (p < 0.005). No significant changes in AMPK (p = 0.724) and PGC-1α (p = 0.794) protein levels were observed between exercised and sedentary rd10 mice. These findings suggest that voluntary exercise enhances photoreceptor survival in RP by increasing serum adiponectin levels, potentially contributing to neuroprotection. Elevated retinal adiponectin appears linked to RP pathology rather than exercise-induced changes. This study highlights the therapeutic potential of exercise in RP and identifies adiponectin as a promising target for further investigation into neuroprotective mechanisms and treatments.